Thromboelastometry-Based Profiling of Haemostatic Alterations in Neonatal Sepsis by Causative Pathogens - Rozeta Sokou; Eleni A. Gounari; Konstantina A. Tsante; Aikaterini Konstantinidi; Maria Lampridou; Martha Theodoraki; Anastasios G. Kriebardis; Sotirios P. Fortis; Nicoletta Iacovidou; Andreas G. Tsantes (Antibiotics)
Background: Neonatal sepsis is a serious condition with high mortality, especially in premature and low-birth-weight neonates. This study aims to examine whether the haemostatic profile of neonates with sepsis defers depending on the type of bacteria (Gram-positive or Gram-negative), by using the method of Rotational Thromboelastometry (ROTEM). Methods: This single-centre prospective cohort study was conducted on 128 neonates with sepsis, including 95 cases caused by Gram-negative pathogens and 33 cases caused by Gram-positive bacteria. All participants were hospitalised in the Neonatal Intensive Care Unit (NICU). ROTEM parameters were compared between neonates with Gram-positive and Gram-negative infections. Results: The ROTEM parameters were found to be significantly different between neonates suffering from Gram-positive versus Gram-negative infections, with Gram-positive pathogens associated with an increased clotting potential compared to Gram-negative pathogens. This is reflected in the higher ROTEM values such as A10, α-angle, and MCF in the EXTEM and INTEM assays. Multivariant analysis showed that Gram-positive infections were linked to increased clot thickness at 10 min (coefficient: 8.9, CI: 2.8–15.0, p = 0.004), higher maximum clot stability (coefficient: 10.4, CI: 4.3–16.6, p = 0.001), and a bigger α-angle (coefficient: 8.0, CI: 2.7–13.2, p = 0.003). Similar findings were observed in the INTEM assay parameters. Conclusions: Neonatal sepsis caused by Gram-positive bacteria leads to a hypercoagulable haemostatic state, whereas neonates with sepsis caused by Gram-negative bacteria exhibit a more hypocoagulable profile and a higher incidence of haemorrhagic episodes. These findings provide valuable insights into the haemostatic disorders associated with sepsis, and may aid in developing an individualised approach for the treatment of those disorders, dependent on and adapted for the specific type of causative organism.